2021
DOI: 10.1016/j.xcrm.2021.100245
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive analysis and resource to use CRISPR-Cas13 for broad-spectrum targeting of RNA viruses

Abstract: Highlights d A web resource for using CRISPR-Cas13 to target broad RNA virus families d A bioinformatic tool to analyze efficiency and specificity of virus-targeting crRNAs d A minipool of crRNAs can target 90% of human-infectious RNA viruses d Validated crRNAs are predicted to target newly emerging SARS-CoV-2 variants

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 39 publications
1
25
0
2
Order By: Relevance
“…Specifically, they observed that the decrease in the percentage of SARS-Cov-2 reporter-positive cells correlated significantly with the predicted targeting efficiency score of crRNAs and with the viral RNA abundance. These results validated their prediction algorithm for the targeting efficiency of crRNAs for the viral genome (Lin et al, 2021).…”
Section: Development Of Genome Editing Therapy For Sars-cov-2supporting
confidence: 57%
See 3 more Smart Citations
“…Specifically, they observed that the decrease in the percentage of SARS-Cov-2 reporter-positive cells correlated significantly with the predicted targeting efficiency score of crRNAs and with the viral RNA abundance. These results validated their prediction algorithm for the targeting efficiency of crRNAs for the viral genome (Lin et al, 2021).…”
Section: Development Of Genome Editing Therapy For Sars-cov-2supporting
confidence: 57%
“…The in silico analysis showed that a minimal set of 14 crRNAs can target >90% of human-tropic viral genomes. Furthermore, by co-transfecting plasmids containing one of five predicted crRNAs and SARS-CoV-2 reporters into A549 lung epithelial cells, Lin et al (2021) validated the PAC-MAN strategy. Specifically, they observed that the decrease in the percentage of SARS-Cov-2 reporter-positive cells correlated significantly with the predicted targeting efficiency score of crRNAs and with the viral RNA abundance.…”
Section: Development Of Genome Editing Therapy For Sars-cov-2mentioning
confidence: 88%
See 2 more Smart Citations
“…These models predict on-target cleavage by measuring knockdown efficacy or indel frequency, and several 18,19 have focused on predictions for CRISPR-Cas13 enzymes using manually-defined features; Cas13 enzymes have applications in diagnostics and are our modeling focus in this work. Subsequent studies 20,21 have applied one of these models 18 to improve Cas13d guide design for viral RNA knockdown, having use in antivirals. To our knowledge, our modeling is the first that applies deep learning to predict Cas13 guide activity.…”
Section: Introductionmentioning
confidence: 99%